Competency framework for hospital pharmacy residency: a scoping review (Research, Society and Development, 2021)
The training and roles of pharmacists around the world are undergoing drastic changes. In the hospital environment, pharmaceutical care services must incorporate hospital pharmacy management necessities, which must consider the constant technological and process innovations. However, there is a scarcity of studies exploring how pharmacy residency programs real experiences in hospitals can improve these essential competencies. This scoping review allowed an overview of the pharmacy residency programs' competency framework's scientific production in the world. These documents review about training programs in the world showed that U.S. programs have teaching processes that evaluate resident's development to certify the program structure to qualify them. Australian and Canadian studies demonstrated advances in the search for pharmacy residents' qualifications with competency-based curricula. It highlighted that a structured and evidence-based approach to these programs' curricula is required and still has ample space in several countries to improve hospital pharmacists' training through residency programs. The most appropriate is that the programs are evaluated in terms of educational results by measuring residents' involvement by considering the course, tutors, and other program components.